Preparation of Microwave Multi-Adsorbent Nanocomposites Based on Copper, Iron Carbonyl, Carbon Nanofiber, Graphite Nanoflake and Polypyrrole - Hossien Hosseini, Seyed; Azimi, Ali; Sadat Hosseini, Sama (Journal of Advances in Nanotechnology, 2020)
The composites of Cu, Carbonyl iron (CI), carbon nanofiber (CNF), graphite nanoflake (GNF)/polypyrrole (PPy) and [(Cu-CI-CNF-GNF) 0.5-PAA]-PPy0.5 were synthesized via different methods by in-situ polymerization on the surface of nanoparticles (NPs) with core-shell structure. This paper describes a method for polyacrylic acid (PAA) coating of NPs in aqueous solution. Then PPy coating was performed by template polymerization on NPs-PAA. Morphology, magnetic and conductivity properties were observed via scanning electron microscopy (SEM), vibrating sample magnetometer (VSM) and four probe method, respectively. The microwave characterization of nanocomposite was evaluated through arch test based on a network analyzer. The PPy nanocomposites possessed the excellent microwave multi absorbers properties in 2-18 GHz. It was also found that nanocomposites with 50% w/w and light weight exhibit good microwave absorbing properties in 2-3 GHz and 5-14 GHz frequency, so can be used to cellphone, radio frequency and radar shielding.
Keywords: Nanocomposites; Cu; Carbonyl iron; Carbon nanofiber; Graphite nanoflake; Polypyrrole; Microwave; Multiabsorbers